PENGARUH STRUKTUR AUDIT, INDEPENDENSI, DAN PROFESIONALISME TERHADAP KINERJA AUDITOR (STUDI PADA INSPEKTORAT ACEH) - Dita Nurul Aurani; Nita Erika Ariani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to determine how much influence audit structure, independence and professionalism have on auditor performance at the Aceh Inspectorate. The population in this study were all auditors who worked at the Aceh Inspectorate Office, totaling 50 auditors. This study uses a non-probability sampling technique with the census method so that the entire population of 50 respondents is used as a sample. The data used is primary data through the distribution of questionnaires. The statistical test used multiple linear regression analysis with the help of SPSS version 26 application. The results showed that the coefficient of determination (R2) was only 50.3%. The results of this study indicate that there are many other variables that affect the performance of the auditor. However, of the three variables tested, the audit structure is the variable that has the most influence. The use of a qualified audit structure through the procedures and techniques applied by the auditors greatly affects the quality of the audits produced by the auditors so that their performance becomes better. In order for the research to be more meaningful, further researchers should examine other independent variables such as ethics, work performance, integrity, career development, work experience, years of service, knowledge, and credibility of an auditor.